Pancasila and Economy Prophetic: the Reconstruction Efforts of Indonesian Economic Law - Nurjannah Septyanun; Tin Yuliani (Law Doctoral Program Universitas Muhammadiyah Surakarta, 2020)
Purphose: The importance of the transcendental paradigm, able to change the demoralization of the economic sphere, affects the changing economic goals of Pancasila. Methodology: Using normative legal research, with paradigmatic approaches and using qualitative descriptive analysis. Finding: The symbolic phenomenon of religious rituals is not merely ritualism in the concept of civil religion. But able to penetrate the particulate partition of the operational dimension. Similarly, the prophetic paradigm, with its prophetic ethics in terms of liberation, humanization, Transcendence, gives space to the fundamental beliefs of society in economics. Civil religion minimizes the ongoing dominance, hegemonic, and exploitative of anti-humanity. The prophetic paradigm and civil religion are capable of being great energy for the realization of the idealism of Pancasila, the first of the transcendental meaning. Importance: The transcendental dimension, of the first Sila, being a turning point. The importance of awareness of the community, and the legal traveler for the reconstruction of Indonesian economic law to realize the social justice of Pancasilais. Originality/Novelty: The Prophetic and civil religion paradigms, becoming one of the bids on economic demoralization. Keyword: Civil Religion; Profetic ethics; Pancasila; Indonesian economic law.